Burn Wound Healing Activity of Ethanol Extract of Jackfruit Leaves (Artocarpus heterophyllus Lmk.) in Sprague Dawley Male Rats - Solihah, Indah; Herlina, Herlina; Mareta, Fauzia (Jurnal Fitofarmaka Indonesia, 2024)
Burn wounds have the potential to become infection, dehydration, and serious complications if not treated properly. Jackfruit leaves (Artocarpus heterophyllus Lmk.) contain secondary metabolites such as flavonoids, tannins, saponins, and steroids which has big potential to accelerate of burn wound's healing. The purpose of this study is to learn more about the effect of jackfruit leaves ethanol extract application on the burn wound healing. The experimental animals were 25 Sprague Dawley rats separated into five groups: negative control group, positive control group, and test groups G1 (94 mg/Kg BW), G2 (188 mg/Kg BW), and G3 (376 mg/Kg BW). The wound area, wound recovery (%), and wound healing time were all measured. To determine the difference on a given day of observation, wound area data were evaluated using a one-way ANOVA test. The ethanol extract of jackfruit leaves (Artocarpus heterophyllus Lmk.) was found to have an effect on burn healing. On the 14th day, the percent recovery values for burns in the positive control, negative control, G1, G2, and G3 groups were 89.9%, 76.5%, 88.8%, 87.2%, and 100%, respectively. Treatment group 3 had the quickest burn healing time and the highest percentage of recovery.